The Literary Criticism and Memoirs of Juan Ramón Jiménez - Allen W. Phillips (Studies in 20th & 21st Century Literature, 1983)
Equally as demanding of others as he was of himself, Juan Ramón Jiménez conceived of literary criticism as a serious and exacting task. The critic and the poet, standing side by side, are devoted to complementary activities of mutual enrichment. However fragmentary and partial the critical opinions of Juan Ramón may be (also outspoken and polemical in nature), they are invaluable as a personal historical and aesthetic guide to about fifty or sixty years of Hispanic literary development (1900-1960). Not to take them into account is to fail to recognize a highly important aspect of his total artistic personality. These varied critical texts are a product of a first rate intelligence and the sensibility of a writer of consummate discrimination who was endowed not only with an excellent memory but also a very special talent for appreciating the authentic. Juan Ramón as a critic is quick to praise (San Juan, Bécquer, Dario, Unamuno and Machado) and at the same time strong in his censure of certain contemporaries. Several recently collected volumes of miscellaneous critical materials have resolved the bibliographical muddle for the initial study of this fundamental aspect of the poet, but still particularly important are the expressionistic portraits of Españoles de tres mundos, longer tributes to Valle, Ortega and Villaespesa as well as the extensive lectures delivered in his latter years. Examination of these pages gives us an historical and creative overview of the period in which he lived and worked in addition to original considerations about the evolution of Hispanic poetry. Of course, one of the constant focal points of his literary criticism was the modernist epoch of his early days, a movement or attitude which he considered to be a modern twentieth century renaissance. Together with detailed study of these two areas of historical and aesthetic nature, in the ensuing pages some conclusions are pointed out as to the essence of poetry according to the theories of Juan Ramón Jiménez, who always differentiated between poetry and literature, finding in great poetry emotive depth and spiritual authenticity.
Keywords: literary criticism; memoir; Juan Ramón Jiménez; Españoles de tres mundos; Valle; Ortega; Villaespesa; Hispanic poetry; modernism; modernist epoch; history; aesthetics; spiritual